Statistics and probability for engineering applications with Microsoft Excel - DeCoursey, W. J. (William J.) (Burlington, MA : Newnes, 2003)
More than ever, American industry especially the semiconductor industry is using statistical methods to improve its competitive edge in the world market. It is becoming more imperative that graduate engineers have solid statistical know-how, yet engineers in industry typically are not well-prepared to use statistics and they are fuzzy about how to apply statistical tools and techniques. This valuable reference makes statistical methods easier and more accessible to engineers. Although the book can be read sequentially, like a normal textbook, it is designed to be used as a handbook, pointing the reader to the topics and sections pertinent to a particular type of statistical problem. It contains the following features: * Covers all major topics treated in a standard college engineering statistics course, but minimizes the mathematical derivations and focuses on practical applications * Uses real data sets/case studies taken from electronics, electrical engineering, and other engineering fields, such as mechanical and chemical engineering * Contains numerous software examples using the powerful statistical functions of Excel In addition, the book provides an "engineering problem solver" section that directs the reader to the relevant section of the book for the problem they are trying to solve. The accompanying CD-ROM contains the Excel data sets for the examples and case studies given in the book, along with other statistical tools and software. * Filled with practical techniques directly applicable on the job * Contains hundreds of solved problems and case studies, using real data sets * Avoids unnecessary theory.
Introduction : probability and statistics -- Basic probability -- Descriptive statistics : summary numbers -- Grouped frequencies and graphical descriptions -- Probability distributions of discrete variables -- Probability distributions of continuous variables -- The normal distribution -- Sampling and combination of variables -- Statistical inferences for the mean -- Statistical inferences for variance and proportion -- Introduction to design of experiments -- Introduction to analysis of variance -- Chi-squared test for frequency distributions -- Regression and correlation.
Includes bibliographical references and indexes.
Keywords: Microsoft Excel (Computer file).; Engineering -- Statistical methods; CD-ROMs.; Electronic books